Efficiency of Triple Antibiotic Mixture and Propolis as Intracanal Medication in Revascularization process in immature apex: A clinical study - Tariq Yehia Abdelrahman Mohamed Yehia; Salma El-Ashry; Kareem El- Batoty; Soha El-Hady (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2019)
Introduction: The aim of this clinical study was to evaluate the effect of different antibacterial combinations on the outcome of revascularization process in permanent anterior immature teeth. Methods: Immature necrotic permanent maxillary incisors (n = 40) of patients 8-18 years old were divided into 4 groups according to the intracanal medicament: group 1 was treated with Triple Antibiotic Paste (TAP), group 2 was treated with Ciprofl oxacin + Propolis paste (CP), group 3 was treated with Ciprofl oxacin + Metronidazole paste (CM), group 4 was treated with Propolis + Metronidazole paste (PM). Cases were followed at regular intervals up to 18 months clinically and radiographically.